The Influence of Brand Image, Price, and Product Quality on Purchasing Decisions on Samsung Brand Smartphone Products (A Study on Students of UPN "Veteran" East Java) - Zhusuf Falhamdany; Maharani Ikaningtyas (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study contains the influence of brand image, price, and product quality on purchasing decisions on Samsung brand smartphone products (a study on students of UPN "Veteran" East Java). This study aims to determine the influence of brand image, price, and product quality on purchasing decisions. The type of research used is quantitative, with a survey method that assesses Samsung Smartphone products in a questionnaire with a specific assessment. The questionnaire data in this study was processed using SPSS software. The population in this study, namely users who buy/use Samsung Smartphones among UPN "Veteran" East Java students, totaling 22.976 students. The sample used was 156 respondents. Meanwhile, the sampling technique in this study uses a nonrandom side/nonprobability sampling technique with several sample criteria for respondents used for the study, namely students of UPN "Veteran" East Java and have bought/used Samsung Smartphone products with data collection through the distribution of Google Forms. The results of the analysis in this study, namely Brand Image (X1), have a positive and significant effect on Purchase Decision (Y) on Samsung brand smartphone products in the study of UPN “Veteran” East Java students. Price (X2) has a positive and significant effect on Purchase Decision (Y) on Samsung brand smartphone products in the study of UPN “Veteran” East Java students. Product Quality (X3) has a positive and significant effect on Purchase Decision (Y) on Samsung brand smartphone products in the study of UPN “Veteran” East Java students. Brand Image, Price, and Product Quality (X1, X2, and X3) simultaneously have a positive and significant effect on Purchase Decision (Y) on Samsung brand smartphone products in the study of UPN “Veteran” East Java students.